PENGARUH BELANJA BARANG OPERASIONAL TERHADAP ASET TETAP DI KEMENTERIAN ATR/BPN KANWIL JABAR PERIODE 2014 – 2018 - Komarudin (Jurnal Co Management, 2019)
This research is aimed to know the influence of goods expenditures operational to the fixed asset at Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional Kantor Wilayah Jawa Barat Periode 2014-2018. The method used in this research was quantitative method and data was obtained from interviews, observations, documentations, and literature study which had realtions to the subjects. Problems found were: too many the fixed assets are damaged, and the room is too narrow. This research indicated that the influence of goods expenditures to the fixed asset at Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional Kantor Wilayah Jawa Barat coming at 90,2% and the rest was influenced by other factors. The suggestions given are: replacing the fixed assets that have better quality, function, and benefits, and renovating rooms that have workloads.